Implementation of Black and Wiliam’s Formative Assessment Framework in The Merdeka Curriculum: Enabling Factors and Challenges in Elementary Education - Kiki Fatmawati; Umil Muhsinin (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2026)
Formative assessment is positioned as a core component of learner-centred instruction in the Merdeka Curriculum, however, its implementation in elementary schools/madrasah ibtidaiyah (SD/MI) remains constrained. This study analyzes the implementation of formative assessment based on Black & Wiliam (2009) framework, with a focus on the enabling and contraining factors shaping its practice in SD/MI. A qualitative approach with a collective case study design was employed across five schools implementing the Merdeka Curriculum. Data were generated through non-participant observation, semi-structured interviews, and document analysis and analyzed thematically across cases. The findings show that formative assessment practices are enabled by teachers’ assessment experience and literacy, principals’ academic supervision, student engagement, and the availability of supportive curriculum resources. Conversely, implementation remains limited by restricted instructional time, large class sizes, the dominance of summative assessment, and weak mastery of reflective assessment strategies, particularly self-assessment. These findings suggest that formative assessment in SD/MI remains developmental in nature and tends to operate more as assessment for learning than as assessment as learning